Egypt: We Are Watching You - Menjou, Leila; El Katsha, Sherief (Egypt : Edkins, Don, 2007)
In 2005 George W. Bush described Egypt as a country which could serve as an example to the Middle East as a democratic state. President Hosni Mubarak, meanwhile, declared the first "free" presidential elections in Egypt in spring of that year. He neglected to mention that opposition candidates had been barred in advance. However, three Egyptian women refused to accept the arrogance of the government and set up a movement called Shayfeen.com – We Are Watching You. Insisting that genuine democracy could only be based on the free will of the people, they began working to increase their fellow citizens' understanding of the fundamentals of democracy. This film records the successes and failures of the movement in the first year of it existence. We see the founders speaking with ordinary people on the street, at demonstrations and remand centres, enjoying small victories and suffering betrayal and frustration. In a country where state propaganda presents an Islamic fundamentalist movement as the only alternative, Egypt: We Are Watching You shows the inner courage of all three women and their belief in democracy, freedom and justice.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films